Diagnoses and nursing Interventions in hypertensive and diabetic individuals according to Orem’s Theory - Priscila Camara de Moura; Luciene Muniz Braga; Camila Santana Domingos; Nayara Vilela Rodrigues; Marisa Dibbern Lopes Correia; Lais Vanessa Assunção Oliveira (Rev Rene)
This study aimed to identify the most prevalent nursing diagnoses in hypertensive and diabetic patients in the Family Health Care Unit, according to Orem’s conceptual model. A descriptive study was conducted from April to November 2013, using a nursing assessment based on Orem’s theory and NANDA-I taxonomy. 16 nursing diagnoses were identified on Universal self-care requisites, nine on Health deviation requisites and two on Developmental self-care requisites, the most prevalent being: “Risk for unstable blood glucose level” (60%), “Ineffective self-care management” (50%) and “Disposition for improved knowledge” (36.6%). Teaching (83.3%) and support/instruction (100%) actions were implemented in nursing care planning. It can be concluded that there is a need to implement nursing activities directed to offering education on Family Health practices.